Inhibitor of MEK1/2, selumetinib, for biliary tract cancer. (October 2011) - Furuse, Junji; Nagashima, Fumio
Evaluation of: Bekaii-Saab T, Phelps MA, Li X et al. Multi-institutional Phase II study of selumetinib in patients with metastatic biliary cancers. J. Clin. Oncol. 29, 2357–2363 (2011). It is necessary to establish effective chemotherapy to improve the survival of patients with biliary tract cancer. Although the useful of some molecular-targeted agents as first-line therapies has been investigated, none have been found to exert satisfactory efficacy. In this article, we report the results of a Phase II study of selumetinib in patients with metastatic biliary cancer. Selumetinib is an inhibitor of MEK1/2 targeting the RAS/RAF/MEK/extracellular signal-related kinase pathway. Three out of 28 patients showed a confirmed partial response, representing a response rate of 12%. The median progression-free survival was 3.7 months and the median overall survival was 9.8 months. The most common toxicities were rash, xerostomia and nausea. Most toxicities were grade 1 or 2, and the most common grade 3/4 toxicities were diarrhea and nausea. All toxicities were manageable and reversible. The results warrant further evaluation of the use of selumetinib in patients with metastatic biliary cancer.